Contribution of Brand Awareness and Brand Characteristics towards Customer Loyalty (A Study of Milk Industry of Peshawar Pakistan) - Khan, Shahzad (Journal of Asian Business Strategy, 2012)
Each and every business firm of the world wants to make their customer loyal towards their company product. But not only one factor is responsible for the loyalty of customers. This research is focused on Peshawar region Customer loyalty towards branded milk. For the purpose two dimensions taken under consideration i.e. Brand awareness and brand characteristics. Brand awareness includes advertising, personal selling, sale promotion and public relation. While brand characteristics include product price, product quality, brand image and packaging. To find out which of these variables contribute how much towards customer loyalty a sample of 200 branded milk users has been contacted from Peshawar region. On the basis of their responses a regression and correlation analysis was conducted. Findings and results of the study shows that brand characteristics has more influence on customer loyalty. Within the brand characteristics quality of the product and brand image is the key factor which contributes more towards customer loyalty. While in case of brand awareness advertising contribute more in comparison of other towards customer loyalty for branded milk.